Foliar anatomy of coffee plants implanted using hydro retainer polymers - Oliveira, Noêmia Karen; de Castro, Evaristo Mauro; Guimarães, Rubens José; Pieve, Leonardo Miari; Baliza, Danielle Pereira; Machado, Janaíne Lopes; Freitas, Tainah (Coffee Science - ISSN 1984-3909, 2014)
The experiment was conducted at the Fazenda Capão dos Olhos, in the municipality of Coqueiral, Minas Gerais, Brazil, in the period of 2009 and 2011. The present work aimed at verifying the changes in the foliar anatomy of coffee plants implanted using hydro retainer polymers. For such, we collected leaves for posterior evaluation of foliar anatomy from plants derived from different treatments (dilutions, doses and location hydrated hydro retainer polymer applications). The experiment consisted of a randomized block design, in the factorial scheme of 4x3x2 plus 1 additional treatment, with four replicates, in a total of 25 treatments (100 plots). The treatments consisted of four doses of the hydro retainer polymer, diluted in 400 liters of water (0.5 kg, 1.0 kg, 1.5 kg and 2.0 kg) in the first factor; three volumes of the hydro retainer polymer previously diluted (1.0 liter, 1.5 liters and 2.0 liters) applied per plant, in the second factor; two application locations (mixed in the planting hill or placed in a hill lateral to the planted seedlings) in the third factor; and an additional treatment as witness, without the use of the hydro retainer polymer. We evaluated the following anatomical characteristics: thickness of the cuticle in the adaxial side, thickness of the epidermis of the adaxial and abaxial sides of the palisade and spongy parenchyma and of the phloem, diameter of the xylem vessels, polar and equatorial diameter of the stomas and relation between the polar and equatorial diameters. We verified that, 24 months after the application of the polymers in the coffee crop, the plants presented changes in the internal structure which favored the hydric relations of the plants.